Encouragement makes good things happen - Schoenaker, Theo J. L. (Brunner-Routledge, 2010)
Describes a courageous and encouraging style of living and focuses on the belief that human encouragement is the most important natural ingredient for the healthy development of human beings. This book explores the negative consequences of discouragement on the individual and on society as a whole. It also discusses what encouragement is